The Role of Extracellular Matrix (ECM) Adhesion Motifs in Functionalised Hydrogels - Anna J. Morwood; Ikhlas A. El-Karim; Susan A. Clarke; Fionnuala T. Lundy (Molecules, 2023)
To create functional tissue engineering scaffolds, biomaterials should mimic the native extracellular matrix of the tissue to be regenerated. Simultaneously, the survival and functionality of stem cells should also be enhanced to promote tissue organisation and repair. Hydrogels, but in particular, peptide hydrogels, are an emerging class of biocompatible scaffolds which act as promising self-assembling biomaterials for tissue engineering and regenerative therapies, ranging from articular cartilage regeneration at joint defects, to regenerative spinal cord injury following trauma. To enhance hydrogel biocompatibility, it has become imperative to consider the native microenvironment of the site for regeneration, where the use of functionalised hydrogels with extracellular matrix adhesion motifs has become a novel, emerging theme. In this review, we will introduce hydrogels in the context of tissue engineering, provide insight into the complexity of the extracellular matrix, investigate specific adhesion motifs that have been used to generate functionalised hydrogels and outline their potential applications in a regenerative medicine setting. It is anticipated that by conducting this review, we will provide greater insight into functionalised hydrogels, which may help translate their use towards therapeutic roles.